The status in Africa of fall armyworm expressing genetic markers related to infestations of pasture, millet, alfalfa, and rice in the Americas - Rodney N. Nagoshi (PLoS ONE, 2025)
The establishment of the fall armyworm (FAW), Spodoptera frugiperda, in Africa is reported to have caused substantial agricultural losses since its detection in 2016 and subsequent spread into Asia and Australia by 2020. Based on the crops being infested, it appears that the population (C strain) primarily responsible for FAW infestations of corn in the Americas is widespread in Africa but there is uncertainty about the status of the R strain that targets pastures, alfalfa, millet, and rice in the United States. The two strains can only physically be distinguished by molecular markers, with single nucleotide polymorphisms (SNPs) in the mitochondrial Cytochrome oxidase subunit I (COI) and nuclear Z-chromosome-linked Triosephosphate isomerase (Tpi) gene demonstrated to consistently identify strains in both American continents. However, the COI and Tpi markers are generally in disagreement in the Eastern Hemisphere. This together with conflicting results from whole genome SNP studies creates uncertainty about the strain composition of this invasive population. In this paper the legitimacy of the Tpi markers is supported and used to not only confirm the existence of the R strain in Africa, but to also provide evidence for the introduction of new R strain variants in western Africa since 2017. These findings have implications on the crops at risk in the Eastern Hemisphere and for understanding how the invasion of Africa by FAW occurred.